PERSEPSI MASYARAKAT TERHADAP RENCANA RELOKASI AKIBAT BENCANA BANJIR (STUDI KASUS KELURAHAN DENDENGAN DALAM, KECAMATAN PAAL DUA) - Frendy Oktavianus Rau; Benu Olfie L. S.; Leonardus R. Rengkung (AGRI-SOSIOEKONOMI, 2016)
This research aimed to describe culture, social, physical, and economy condition, to find out public perception of the relocation plan, and to identify relationship between public perception and influence factors at Lingkungan I. This research was done for three months from Agustus to October 2015 at Kelurahan Dendengan Dalam Lingkungan I, Paal Dua Sub-District, Manado City, North Sulawesi Province. This research uses descriptive qualitative with method or case study approach. Data analysed in quantitative and qualitative with statistical analysis in tabulation, percentage, and scoring and then continued with chi-squared analysis. Result showed that people condition at Lingkungan I after flood disaster didn't affect familty economy which still in passably economy but physical condition changed to weak and socio-cultural condition became good while organization condition (government socialization effort) was in passably condition because public didn't understand enough or had awareness about the relocation plan. People of Lingkungan I, Kelurahan Dendengan Dalam, doubt and didn't agree with resettlement plan of government. Most of the public attitude were attitude of passably economy condition, weaker physical and fixed condition, low and passably good organization condition, and lack of (enough) public awareness about the whole relocation plan. Factors which have connection with public perception at Lingkungan I, Kelurahan Dendengan Dalam such as organization condition (government socialication effort) and the level of knowledge about the whole relocation plan, while economy, physic, and socio-cultural condition were not affect by that.